The use of thymol, carvacrol and sorbic acid in microencapsules to control Salmonella Heidelberg, S. Minnesota and S. Typhimurium in broilers - Stingelin, Giovani Marco; Scherer, Ricardo Simões; Machado, André Costa; Piva, Andrea; Grilli, Ester; Penha Filho, Rafael Casarin (Frontiers in Veterinary Science, 2023)
The control of Salmonella spp. in poultry involves different biosecurity actions and lately has been complicated by the emergence of multidrug resistant serovars. The application of organic acids and essential oils has been used with different approaches due to the antibacterial properties as food preservatives. The use of these molecules in animal feed to control enteric pathogens is a major interest within the poultry industry. The use of a blend containing nature-identical compounds of sorbic acid (25%), thymol (9.5%) and carvacrol (2.5%) microencapsulated in a lipid matrix, was investigated in the present work, for the control of three Salmonella serovars (S. ser. Typhimurium, S. ser. Heidelberg and S. ser. Minnesota). Commercial broilers were challenged at 3 or at 33 days of age. Groups SH-1, SM-1 and ST-1, received treatment in the feed, at 2kg/ton from 1-21 days of age and at 1kg/ton from 35-42 days of age (last week), while groups SH-2, SM-2 and ST-2, were treated only during the last week receiving 2kg/ton. Each treated group had an untreated control group, that was challenged at the same moment with the respective serovar (groups PCH, PCM and PCT). The challenge strains were enumerated in liver and cecal contents, weekly after challenge, at 7, 14, 21, 28, 35 and 42 days-of-age, showing significant reduction at 7 and 14 days of age in all groups that received treatment during the initial phase (p<0.05). Moreover, the body weight was significantly higher at the last experimental day (p<0.05) in chickens that received treatment at the initial and at the final growth stages.